LIBERALISME DALAM FILSAFAT PENDIDIKAN “ SUATU ANALISIS ONTOLOGIS, EPISTIMOLOGIS DAN AKSIOLOGIS - Authar, Tanzil; Walidin AK2, Warul; Silahuddin (Anatesa : Kajian Pendidikan, Sosial dan Keagamaan, 2023)
Educational philosophy is a branch of philosophy that discusses the goals, meaning and methods of education. In this framework, liberalism is one of the views that influences thinking about education. This article is based on a literature review and prepared by collecting information from relevant literature. The data in this research focuses on a simple study of the view of liberalism in educational philosophy. This data collection was obtained from reviewing books, magazines, articles or previous publications. Related to the view that education is important in the process of achieving the main goals of liberalism, there is the view that equality in education must be regulated based on these results. Ontology is a philosophical discipline that studies everything that exists from the aspect of cause and effect. Epistemology is how education can be a shining light in eradicating knowledge poverty and moral poverty with the principle of validity. Axiology is a science that examines the values ​​and norms in the use of science itself, which in this case is related to education.